Agency Conflict dalam Memaksimalkan Kinerja Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia (BEI) - Wijayanti, Monica Chandra; Anggriani, Rini; Dethan, Stevany Hanalyna; Hendri, Wira; Widiyasti, Baiq Dinna (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Agency conflict plays a role in influencing a company's ability to maximize its performance. The performance of pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2016–2023 period has fluctuated. One of the influencing factors is ownership structure, which impacts the effectiveness of corporate management. This ownership structure is divided into three dimensions: ownership concentration, institutional ownership, and managerial ownership. This study aims to identify and examine the partial and simultaneous effects of that three dimensions on the Performance of Pharmaceutical Sub-Sector Companies. The research employs a causal associative approach using a quantitative methodology, utilizing panel data analysis techniques involving 10 pharmaceutical sub-sector companies over an eight-year observation period. Consequently, 80 sample data points were processed using E-Views 12. The tests conducted in this study include classical assumption tests (normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test) and hypothesis tests (t-test, F-test, and R² test). The results indicate that, partially, ownership concentration and managerial ownership do not significantly affect company performance, whereas institutional ownership has a positive simultaneous effect on company performance. The simultaneous test results show that the three independent variables in this study collectively influence company performance by 40%.